Coaching Program to Develop Teachers’ Pedagogical Competence: a Description of Experience - Siti Tarwiyah; Nuna Mustikawati Dewi; Lulut Widyaningrum (Universitas Islam Negeri Walisongo Semarang, 2018)
The educational practices of Indonesian schools today are executed under the 2013 Curriculum. Although it has been implemented 5 years, problems of its realization are still found. It is partly due to insufficient knowledge and skills of teachers in terms of planning, implementing, assessing and evaluating a sequence learning processes. Coaching is one of professional development programs which may enhance teachers’ skill and will. It emphasizes on good relationship between the coach and the coachee so that they can work as coworkers so that it makes the coachee feel at ease to consult the problems of learning. This paper shares some experiences of a coaching program to develop 7 teachers’ pedagogical competence of 5 Islamic Junior High Schools in Semarang. The implementation covers assessing needs, developing materials, designing assessment, presenting materials, implementing the materials, and making reflection.